Implementation of a partially decentralized control architecture using wireless active sensors. (17th January 2020) - Debattisti, N; Bacci, M L; Cinquemani, S
Abstract: This paper deals with the development of a vibration control architecture in which many stand-alone active dampers are involved. Each device is able to independently perform the control task, since it is embedded with sensors, an inertial actuator and a microcontroller, in which the control algorithm is implemented. The aim of this architecture is to improve the performance of a decentralized control strategy through a partial sharing of data between devices. The proposed control solution is based on the optimal control theory; the Linear Quadratic Regulator works with the full-state of the system, which is not available in many applications. In order to provide the entire state vector, state estimation is implemented in each device. A state recovery algorithm is adopted to improve the quality of the estimation without placing a hefty burden on the wireless channel. Numerical analysis is made in order to study the advantages of this method. Finally, the proposed solution is validated with experimental results from a clamped–clamped beam.